2019
DOI: 10.1177/0284185119875631
|View full text |Cite
|
Sign up to set email alerts
|

A small bifurcated self-expanding metallic stent for malignant bronchial fistula or severe stenosis around the upper left carina

Abstract: Background Bifurcated self-expanding metallic stents have mainly been primarily used for the treatment of airway disease around the main carina, but few studies have reported the use of small bifurcated stents to treat malignant bronchial fistula or severe stenosis around the upper left carina. Purpose We aimed to determine the safety, feasibility, and efficacy of small metallic bifurcated stent placement in the upper left carina. Material and Methods Twenty-two patients with malignant bronchial disease were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…And the complications are similar among two types of the stents in most conditions which included migration, granulation, diminished mucociliary clearance and patient intolerance. Previous studies have reported the complication rate of 16.1-40.9% in re-establishment of airway with Y stents and 31.3-44.4% with SEMS (15)(16)(17).…”
Section: Discussionmentioning
confidence: 97%
“…And the complications are similar among two types of the stents in most conditions which included migration, granulation, diminished mucociliary clearance and patient intolerance. Previous studies have reported the complication rate of 16.1-40.9% in re-establishment of airway with Y stents and 31.3-44.4% with SEMS (15)(16)(17).…”
Section: Discussionmentioning
confidence: 97%
“…All patients have to inhale 0.9 saline with nebulizer four times a day. The stent of this type is not self-expanding and we have to place it correctly the first time and use the inner balloon to expand it with 8-12 bars [22,23]. Afterward maybe the stent can be removed and replaced by a bigger stent (7 × 22 mm iCAST, 10 mm Dumon) after three months in order to avoid the adverse effects of a metallic stent (Figure 3).…”
Section: Application For Lobar Stenosismentioning
confidence: 99%